Pertarungan Ideologi Politik Dan Politik Identitas Dalam Kontestasi Elektoral Indonesia - JULIA SAFITRI; JESIKA MERANI PUTRI; LUTFI TRI ARYANI (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Indonesia’s electoral landscape has increasingly reflected a complex interplay between ideological contestation and identity-based politics. This study aims to analyze how political ideologies and identity narratives are mobilized during electoral competition, as well as their implications for democratic consolidation. Using a qualitative approach with literature review and case analysis of recent elections, this research examines patterns of political messaging, campaign strategies, and voter behavior. The findings indicate that while ideological discourse such as nationalism, religious values, and economic orientation—remains present, it is often overshadowed by identity politics rooted in ethnicity, religion, and social group affiliations. Political actors strategically employ identity markers to build emotional connections with voters, sometimes intensifying polarization within society. This dynamic not only shapes electoral outcomes but also affects the quality of democracy by shifting focus from policy-based debates to symbolic and identity-driven narratives. The study concludes that strengthening political literacy and institutional frameworks is essential to ensure that electoral competition remains substantive rather than divisive. The implications highlight the need for inclusive political communication and regulatory mechanisms to mitigate the risks of identity-based fragmentation in Indonesia’s democratic process.